Isolation and characterization of a molybdenum-reducing Bacillus pumilus strain lbna (Journal of Environmental Microbiology and Toxicology, 2013)
The reduction of heavy metals by microorganisms has an important role in biological system and also in the cycling of metals in the environment to remove its toxic effects in soil and wastewater. A molybdenum-reducing bacterium was isolated from soil obtained from Seri Kembangan, Selangor. This isolate is Gram positive bacteria and was identified as bacillus pumilus strain based on 16s rRNA gene sequencing. Molybdenum reduction is optimally supported by glucose at 1.0% (w/v). The optimum phosphate and molybdate concentrations for molybdate reduction in Bacillus pumilusstrain Lbnawas between 2.5 and 5 mM phosphate and 40 mMmolybdate. Molybdate reduction is optimum at 37 ÂºC. The metal ions arsenic, lead, zinc, silver, cadmium, chromium, mercury and copper caused 33.7, 36.0, 51.2, 60.5, 63.9, 91.3, 92.3 and 98.0% inhibition to molybdenum reduction.
Keywords: Bacillus pumilus Molybdenum Heavy metals